Diagnosis of Epilepsy Following Paroxysmal Event - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The accuracy of the initial diagnosis after one or more paroxysmal events is described as part of the Dutch Study of Epilepsy in Childhood (DSEC), a prospective hospital-based study of children with newly diagnosed possible single or multiple seizures.